Field Evaluation Of Fungicide Againstanthracnose And Powdery Mildew Disease Of Mango Cv. Alphonso (Journal of Plant Disease Sciences, 2020)
An investigation was conducted to study the efficacy of common and newer molecule fungicide against powdery mildew (Oidium mangiferae) and anthracnose (Colletotrichum gloeosporioides) disease of mango under natural field conditions at Regional Fruit Research Station, Vengurle, Mahashtra, India during 2017-18 and 2018-19. Among the different treatments, pooled results revealed that newer molecule propiconazole 13.9 (15% w/v) + difenoconazole 13.9% w/w (15% w/v) EC @ 1.2 ml/liter of water recorded significantly lower per cent disease index of anthracnose (7.10) and powdery mildew (8.47) which resulted 82.36 and 83.67 per cent disease control respectively over control. Traditional old chemical carbendazim 12% + mancozeb 63% WP significantly reduced the disease incidence of anthracnose and powdery mildew of mango over control bur new generation chemicals propiconazole 13.9 (15% w/v) + difenoconazole 13.9 % w/w (15% w/ v) EC was found more effective.
Keywords: Mango; Anthracnose; Powdery mildew; Fungicides and Efficacy